Terapi Bekam Menurunkan Nyeri Dismenore - Setyawati, Irni; Fatmawati, Nurul; Ulya, Yadul; Maya Herlina, Siskha; Husyanti, Sarah (Journal of Fundus, 2023)
Dysmenorrhea is abdominal pain during menstruation which usually occurs at the beginning of the menstrual cycle. There are several ways to deal with dysmenorrhea that are usually done by adolescents, namely pharmacological and non-pharmacological ways. One of the non- pharmacological ways is the traditional way with cupping therapy. Cupping therapy is carried out by sucking the skin through suction cups to reduce pain during dysmenorrhea. The author wants to conduct a literature review on the topic of cupping therapy to reduce dysmenorrhea pain. This study used the literature review method with data in the form of Sinta indexed journal articles for at least the last 10 years, from 2013 to 2023 which were accessed via the Google Scholar page. In identifying the title found 6 articles and in the final stage only 3 articles that can be used. Wet or dry cupping therapy can reduce the level of dysmenorrhea pain in adolescents. Further research is needed on the effectiveness of dry or wet cupping to reduce dysmenorrhea pain.